Blockchain, a Panacea for Development Accountability? A Study of the Barriers and Enablers for Blockchain's Adoption by Development Aid Organizations - Rugeviciute, Aiste; Mehrpouya, Afshin (Frontiers in Blockchain, 2019)
In recent years, the term “blockchain” has been sprinkled widely and the hype around it attracts billions in investments. The promises that this technology can be a solution to many of society’s present problems have drawn attention from all sectors, including development aid. The historical recognition of potential and actual corruption resulting from development aid sparked a rise in demands for more transparency and accountability in this sector. So far, there have been reflections in different academic disciplines about the potentials of Blockchain in this area. However, little empirical investigation has been conducted to understand the technological and institutional enablers and barriers for its adoption in the development aid sector. This study aims to take initial steps towards such understanding with a focus on the potential role for Blockchain Technology in financial aid flows through an analysis of the donors’ perspectives. Our research is based on diverse qualitative material. It relies on reports and discussion papers produced by donor organizations and on case studies of two start-ups focused on introducing Blockchain into development aid management. Besides a body of archival qualitative material, we conducted interviews with different actors in the development financing field. Based on an inductive qualitative methodology, we grouped findings into three categories of barriers and enablers: discursive, technological and institutional. Our study shows that discourses about Blockchain Technology vary a lot and there is a lack of common framing of its definition, attributes, and insufficient engagement around these concerns between different actors. Overall, the ability to increase the visibility of cash flows and a potential to reduce administration costs were perceived to be the most useful features, combined with the desire/need expressed by some donors to be at the forefront of technological developments. Lack of understanding about this technology and fear of its complexity and related security challenges were the most cited technological obstacles. Lack of institutional structures for rule making and for enabling field-level exchanges and knowledge production around Blockchain-based projects is currently the most prominent challenge to its diffusion and wider adoption.